Empowering Communities Through Innovative Health Education: Strategies for Sustainable Health Improvement - Chander Mohan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Health education stands as a critical pillar in the architecture of public health, instrumental in shaping behaviors, enhancing preventive care, and improving health outcomes across communities. This paper delves into a comprehensive analysis of various health education strategies, highlighting innovations that have proven effective in different socio-cultural environments. By integrating case studies, theoretical models, and technology, the research identifies key approaches that can be scaled and adapted for broad application. The study reveals the significance of culturally sensitive, technology-enhanced educational methods, and peer-led initiatives in fostering sustainable health behavior changes. It also proposes a framework for ongoing adaptation and evaluation of health education programs, aiming to empower communities through knowledge, ultimately contributing to a healthier global population.